2014
DOI: 10.1021/ic402702z
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical Analysis of Ruthenium(II) Sensitizers of 1,2,3-Triazole-Derived Mesoionic Carbene and Cyclometalating Ligands

Abstract: A series of heteroleptic bis(tridentate) ruthenium(II) complexes bearing ligands featuring 1,2,3-triazolide and 1,2,3-triazolylidene units are presented. The synthesis of the C^N^N-coordinated ruthenium(II) triazolide complex is achieved by direct C-H activation, which is enabled by the use of a 1,5-disubstituted triazole. By postcomplexation alkylation, the ruthenium(II) 1,2,3-triazolide complex can be converted to the corresponding 1,2,3-triazolylidene complex. Additionally, a ruthenium(II) complex featuring… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
63
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(67 citation statements)
references
References 98 publications
3
63
0
1
Order By: Relevance
“…250 Comparing structure 145 with its 1,4-disubstituted counterpart (Scheme 58), the authors found significant differences in the spectral properties of the molecules, where blue shifts for 145 relative to the corresponding 1,4-isomer in the absorption and emission spectra were attributed to a lesser degree of conjugation in Ruthenium(II) polypyridyl complexes, where one or two pyridyl ligands were replaced by 1,5-disubstituted triazoles, were synthesized by Schubert and co-workers, 252 and alkylation of the triazoles with methyl iodide also gave access to ruthenium triazolylidene complexes. The electrochemical and photochemical properties of 146-148 ( Fig.…”
Section: Figure 30mentioning
confidence: 99%
“…250 Comparing structure 145 with its 1,4-disubstituted counterpart (Scheme 58), the authors found significant differences in the spectral properties of the molecules, where blue shifts for 145 relative to the corresponding 1,4-isomer in the absorption and emission spectra were attributed to a lesser degree of conjugation in Ruthenium(II) polypyridyl complexes, where one or two pyridyl ligands were replaced by 1,5-disubstituted triazoles, were synthesized by Schubert and co-workers, 252 and alkylation of the triazoles with methyl iodide also gave access to ruthenium triazolylidene complexes. The electrochemical and photochemical properties of 146-148 ( Fig.…”
Section: Figure 30mentioning
confidence: 99%
“…Heteroleptic Ru(II) complexes with carboxylate-appended terpy of 52 only gave modest power conversions. 153 Anionic 1,2,3-triazolate derivatives of btp have also been reported, such as 53. These ligands have increased s-and p-donor strengths, shifting the MLCT of Ru(II) complexes to longer wavelengths.…”
Section: Btp Derivatives For Photosensitiser and Dssc Applicationsmentioning
confidence: 99%
“…[418] Functionalized bis-1,2,3-triazole "click" ligands with a spacer between the two heterocycles have been shown to self-assemble with palladium(II) into quadruply stranded cages where two palladium ions and two bis-triazoles form a rectangle. [419] Ruthenium(II) complexes of 1,2,3-triazolate based tridendate ligands show promising properties for their use as dyes in solar cells. [420] 1,2,3-Triazoles and derivatives are a special class of heterocycles with a broad spectrum of applications.…”
Section: Isothiocyanate Addition Productsmentioning
confidence: 99%